The Journey for The Certified Dam Safety Inspector (CDSI) Program in Malaysia - Sidek L.M.; Noh M.N.M.; Ashworth A.; Ahmad S.A.; Wong P.; Basri H.; Omar J.; Ng S.K.; Wightman D. (Springer Science and Business Media Deutschland GmbH, 2024)
Dams for water storage, irrigation, and/or hydropower generation continue to have an important role in safely and sustainably managing our water, food, and energy supply security. Designing and operating dams to minimize impacts on social and environmental values and to ensure the longevity of their safe operation is critical. There is also a growing understanding utilities and asset owners that safe operation relies on people having the right skills and the competency to do so. Thus, the quality and capability of peoples assets become equally important as the physical assets. With a high proportion of dams for a country of its size and many ageing assets, the Malaysian Government also turned its attention to improving regulation and guidance to operators through MyDAMS in 2017. With the establishment of the Malaysian National Committee on Large Dams (MYCOLD), there has been a focus on building the local capability and capacity to support a long-term future of dam safety in Malaysia. MYCOLD collaborated with the Entura clean energy and water institute (a registered training organization in Australia) to commence a program of certified Dam Safety Inspectors (CDSI). The program had several challenges, not least of which has been continuing through COVID-19 travel restrictions and is the key focus of this paper. The first batch of the program was successfully delivered with a total of 29 certified inspectors in place as a starting point. More work will follow with additional batches and a framework for ongoing training refresh and obligations to ensure experience levels are maintained. The Author(s), under exclusive license to Springer Nature Singapore Pte Ltd. 2023.